Electrical resistance and mold distribution on beef surface as indicators of dry aging. (29th May 2019) - Oh, Jungmin; Lee, Hyun Jung; Yoon, Ji Won; Choe, Juhui; Jo, Cheorun
Abstract: The objective of this study was to investigate the electrical resistance and mold distribution on a dry‐aged beef surface (crust) and to explore the use of these information as an indicator of dry aging. In total, 18 strip loins ( longissimus lumborum ) were dry aged for 35 days. During aging period, electrical resistance and mold distribution on the crust, pH, shear force, and sensory properties (appearance, flavor, tenderness, juiciness, and overall acceptance) of the edible portion of meat were assessed. Electrical resistance ( R 2 = .91, −.72, and .69, respectively) and mold distribution ( R 2 = .81, −.73, and .65, respectively) of the surface were strongly correlated to pH, shear force, and tenderness of dry‐aged beef ( p < .05). Moreover, mold distribution had significant correlation to flavor ( R 2 = .48), among sensory properties. In conclusion, the electrical resistance and mold distribution on beef surface indicate the degree of dry aging, especially in tenderness and flavor.. Practical applications: The manufacture parameters of dry aging have been varied with different meat producers, resulting in different final qualities of dry‐aged beef products. In this study, we suggested the use of indicators for determination of level of dry‐aging in beef including electrical resistance and mold distribution. It can help unexperienced small meat producers to guarantee the suitable degree of doneness of dry‐aged beef, especially in flavor and tenderness.